2012
DOI: 10.1593/neo.12768
|View full text |Cite
|
Sign up to set email alerts
|

Circumventing Cellular Control of PP2A by Methylation Promotes Transformation in an Akt-Dependent Manner

Abstract: Heterotrimeric protein phosphatase 2A (PP2A) consists of catalytic C (PP2Ac), structural A, and regulatory B-type subunits, and its dysfunction has been linked to cancer. Reversible methylation of PP2Ac by leucine carboxyl methyltransferase 1 (LCMT-1) and protein phosphatase methylesterase 1 (PME-1) differentially regulates B-type subunit binding and thus PP2A function. Polyomavirus middle (PyMT) and small (PyST) tumor antigens and SV40 small tumor antigen (SVST) are oncoproteins that block PP2A function by re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(82 citation statements)
references
References 70 publications
5
77
0
Order By: Relevance
“…Methylation Assay-Methylation assays for PP4c and PP6c were performed as previously reported for PP2A (19,56). Briefly, two 20-l aliquots of each cell lysate were prepared.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Methylation Assay-Methylation assays for PP4c and PP6c were performed as previously reported for PP2A (19,56). Briefly, two 20-l aliquots of each cell lysate were prepared.…”
Section: Methodsmentioning
confidence: 99%
“…HDAC3 has been implicated in cancer (53)(54)(55). Recently, it has been shown that LCMT-1 KD promotes cancer phenotypes such as anchorage-independent growth (56). It would be interesting to determine if dysregulation of HDAC3 contributes to the anchorage-independent growth phenotype in LCMT-1 KD cells.…”
Section: Lcmt-1 Differentially Regulates Different Pp4 Holoenzymesmentioning
confidence: 99%
“…In addition, MAPK3 (ERK1) and AKT1 were included in the RRP library as internal controls representing known PME-1 effector proteins (11,23). The relevance of the PC-3 cell model for assessing PME-1 interactome function was validated by robust inhibition of colony growth by PME-1 depletion ( Supplemental Fig.…”
Section: Rrp Analysis Of Pin1mentioning
confidence: 99%
“…5F), further indicating its potential involvement in cancer biology. were included to RRP analysis as previously validated PME-1 effector genes (11,23). FunCoup similarity index (min.…”
Section: Rrp Analysis Of Pin1mentioning
confidence: 99%
“…Specific heterotrimers dephosphorylate and stabilize tumor suppressors, such as p53 (5,6) and p107 (7); thus, PP2A activity is important in cell-cycle regulation and tumor suppression. PP2A has been shown to dephosphorylate positive regulators of cell signaling pathways such as ERK and Akt (8)(9)(10)(11), inhibiting them and promoting senescence or apoptosis. Inhibition of PP2A promotes enhanced cell proliferation, impairment of cell differentiation, malignant cell transformation (reviewed in refs.…”
Section: Introductionmentioning
confidence: 99%